SDG10 - reduce inequality within and among countries - Pandey, Umesh Chandra; Kumar, Chhabi; Ayanore, Martin; Shalaby, Hany R. (Concise Guides to the United Nations Sustainable Development Goals, 2020)
Rising inequalities are a defining challenge of our times and a crucial obstacle to the realization of the SDGs. The need to accelerate steps towards the reduction of growing disparities within and among countries is well realised. Responding to that need, this book aims to understand the types, drivers, consequences and impact of inequalities in broad contexts across groups and individuals, as well as societies and states. Defining inequality as the social, economic and political challenges of our time, the authors examine SDG10 to look ahead at how policy action might engage multiple stakeholders, involve diverse sectors and address gaps between policy and implementation to tackle inequalities and facilitate the advancement of the SDG agenda.